Digoxin Derivatives Sensitize a Saccharomyces cerevisiae Mutant Strain to Fluconazole by Inhibiting Pdr5p - Daniel Clemente de Moraes; Ana Claudia Tessis; Rodrigo Rollin‐Pinheiro; Jefferson L. Princival; José Augusto Ferreira Perez Villar; Leandro A. Barbosa; Eliana Barreto‐Bergter; Antônio Ferreira‐Pereira (2022)
The poor outcome of treatments for fungal infections is a consequence of the increasing incidence of resistance to antifungal agents, mainly due to the overexpression of efflux pumps. To surpass this mechanism of resistance, a substance able to inhibit these pumps could be administered in association with antifungals. Saccharomyces cerevisiae possesses an efflux pump (Pdr5p) homologue to those found in pathogenic yeast. Digoxin is a natural product that inhibits Na+, K+-ATPase. The aim of this study was to evaluate whether digoxin and its derivatives (i.e., DGB, digoxin benzylidene) can inhibit Pdr5p, reversing the resistance to fluconazole in yeasts. An S. cerevisiae mutant strain that overexpresses Pdr5p was used in the assays. The effects of the compounds on yeast growth, efflux activity, and Pdr5p ATPase activity were measured. All derivatives enhanced the antifungal activity of fluconazole against S. cerevisiae, in comparison to fluconazole alone, with FICI values ranging from 0.031 to 0.500. DGB 1 and DGB 3 presented combined effects with fluconazole against a Candida albicans strain, with fractional inhibitory concentration index (FICI) values of 0.625 and 0.281, respectively The compounds also inhibited the efflux of rhodamine 6G and Pdr5p ATPase activity, with IC50 values ranging from 0.41 μM to 3.72 μM. The results suggest that digoxin derivatives impair Pdr5p activity. Considering the homology between Pdr5p and efflux pumps from pathogenic fungi, these compounds are potential candidates to be used in association with fluconazole to treat resistant fungal infections.